Tailored Management of Advanced Esophageal Squamous Cell Carcinoma — Balancing Efficacy and Toxicity with a “Hold Chemotherapy and Keep Immunotherapy” Strategy: A Case Report - Yu-Chieh Lin; Jeng-Shiun Du; Chun-Chieh Wu (Journal of Cancer Research and Practice)
Esophageal squamous cell carcinoma (ESCC) is an aggressive malignancy with a poor prognosis in advanced stages. Pivotal trials including ATTRACTION-3, CheckMate 648, and CheckMate 577 have demonstrated that immunotherapy with nivolumab significantly improved survival and maintained disease control. We report a 59-year-old female with a 3-month history of intermittent nausea, vomiting, and unintentional weight loss of approximately 5 kg. A definite diagnosis of ESCC with distant lymph node metastasis (cT2N3M1, Stage IVB) was confirmed by positron emission tomography and esophagogastroduodenoscopy with biopsy. This report details her clinical course, including chemotherapy, immunotherapy, and radiation therapy. Despite initially achieving complete remission, recurrence was detected during follow-up. A ”Hold Chemotherapy and Keep Immunotherapy” strategy effectively managed advanced ESCC, balancing efficacy and toxicity while preserving quality of life.